Urgensi Penyederhanaan Agenda Sidang Pada Hukum Acara Perdata Di Indonesia - Syahrul Sajidin (Departemen Hukum Perdata, 2018)
Court beside as a judicial institution, have other function to give public service. One of the good and excellent services is realized by the existence of a simple service procedure. One of the most highlighted is that there are still many trial agendas that are considered unnecessary to be delivered directly in front of the panel of judges (during the hearing). Some of these stages include the agenda for reading answers, replicating and duplicating. So that from some of these backgrounds it is necessary to examine the urgency of simplifying the civil procedure law in Indonesia. From the description of the background of the research, the formulation of the problem can be arranged as follows, what is the urgency of simplifying the session agenda by submitting the answers, replicating and duplicating in writing and how is the simpliﬁ cation of the Civil Procedure Law in supporting the implementation of the judicial principle fast, simple and low-cost?. Simpliﬁcation of civil procedural law is expected to be able to reduce the hours of the trial so that with fewer trial agendas the session becomes effective and efficient. In order for the simplification of civil procedural law to be able to bring maximum results, the Supreme Court needs to prepare several things. With the stages of building the system, managing the system, utilizing technology, increasing the role of the business world, developing HR capacity and implementing development in a systematic and measurable manner.